Regulation of growth and dissemination of a human lymphoma by CD44 splice variants. - Bartolazzi, A; Jackson, D; Bennett, K; Aruffo, A; Dickinson, R; Shields, J; Whittle, N; Stamenkovic, I (1995)
CD44 is a polymorphic cell surface glycoprotein, currently proposed to be the principal cell surface receptor for hyaluronan. However, different isoforms of CD44, expressed in human lymphoid tumor cells, appear to have distinct effects on the ability of the cells to attach to hyaluronan-coated surfaces and on their capacity to form tumors in vivo. In the present study, we address the mechanisms that may regulate CD44 isoform-dependent adhesion to hyaluronan. We use a human Burkitt lymphoma, stably transfected with six different alternatively spliced human CD44 isoforms, to determine their potential hyaluronan binding and tumor growth promoting roles. We show that transfectants expressing CD44 splice variants that contain variable exons 6-10, 7-10 and 8-10 adhere to hyaluronan-coated surfaces weakly and that corresponding tumor formation in vivo is delayed with respect to CD44-negative parental cell-derived tumors. Abundant shedding of these three isoforms may play a significant role in determining the rate of tumor development. Transfectants expressing variable exon 3, on the other hand, fail to display CD44-mediated adhesion to hyaluronan, but form bone marrow tumors rapidly following intravenous injection. These observations suggest that different mechanisms regulate CD44-mediated adhesion and tumor growth, and provide evidence that expression of exon v3 may confer novel ligand-binding properties.